Caribbean Report 27-03-1995 - Orr, Carol (anchor); Meeks, Brian (interviewee); Esquivel, Manuel (interviewee); Rush, George (correspondent); Fraser, Tony (correspondent); Huggins, Russell (interviewee); Wyatt, Diana (interviewee); Singh, Rickey (interviewee); Melville, Selwyn (correspondent) (The British Broadcasting Corporation, 1995)
Jamaica's Opposition Leader, Edward Seaga receives the backing of party delegates to continue as JLP Leader. Political analyst, Brian Meeks analyses the situation. The Chairman of Caricom, Belizean Prime Minister Manuel Esquivel, is currently on an official visit to Washington and aims to press the case for Caribbean banana exporters in the face of US opposition to the European Union banana regime. In Bermuda, the House of Assembly gave a final, if not, narrow approval for the independence referendum bill. The number of husbands being beaten by their wives is on the increase in Trinidad and Tobago. Caribbean Media Workers Association (CAMWORK) President, Rickey Singh comments on the political pressure and intimidation of Caribbean journalists.Both Trinidad and Tobago's and Jamaica's hockey teams had to be content with fifth place at the Pan Am Games in Argentina. Selwyn Melville reports on the competition and states that there is still hope for the future.
1. Headlines with Carol Orr (00:00-00:29)
2. Jamaica's Opposition Leader Edward Seaga gets the backing of party delegates to continue as JLP leader (00:30-03:25)
3. Caricom Chairman, Manuel Esquivel takes Caricom banana case to Washington (03:26-05:41)
4. In Bermuda, the House of Assembly gave the independence referendum bill a final approval (05:42-08:07)
Keywords: Jamaica -- Politics and government; Politicians -- Jamaica; Political leadership -- Jamaica; Banana trade -- Caribbean Area; Caribbean Area -- Relations -- United States; United States -- Relations -- Caribbean Area; Bermuda Islands -- Politics and government; Bermuda Islands -- History -- Autonomy and independence movements; Referendum; Family violence -- Trinidad and Tobago; Abused men -- Trinidad and Tobago; Men -- Violence against; Journalists -- Caribbean Area; Press and politics -- Caribbean Area; Local mass media -- Caribbean Area; Hockey -- Caribbean Area; Hockey -- Tournaments -- America; Hockey teams -- Caribbean Area